Development of a duplex Taqman real-time PCR assay for rapid identification of Vibrio splendidus -related and V. aestuarianus strains from bacterial cultures - Saulnier, Denis; De Decker, Sophie; Tourbiez, Delphine; Travers, Marie-agnes (Journal of Microbiological Methods, 2017)
To enable the rapid and accurate identification of Vibrio splendidus-related and V. aestuarianus strains associated with Pacific cupped oyster Crassostrea gigas mortality, we developed a duplex Taqman real-time PCR assay and evaluated its efficacy. This technique proved to be rapid, sensitive, and specific and will be particularly valuable for epidemiologic studies.